Acid-resistant polyquaternary ammonium membrane based on Porxitu interfacial polymerization reaction as well as preparation method and application of acid-resistant polyquaternary ammonium membrane
By carrying out Menschuttekin interfacial polymerization reaction at high temperature and using specific solvents and post-treatment methods, acid-resistant polyquaternary ammonium membranes are prepared, which solves the problems of long production cycle and low water flux, and achieves efficient preparation of thin and stable polyquaternary ammonium membranes, which are suitable for nanofiltration, ion exchange membranes and fuel cell membranes.
Patent Information
- Application Number
- CN202510851082.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2025-09-26
AI Technical Summary
Existing polyquaternary ammonium salt membranes have slow kinetics in the Menschuttekin interfacial polymerization reaction, resulting in long production cycles and low water flux, limiting their large-scale application.
The acid-resistant polyquaternary ammonium membrane is prepared by conducting an interfacial polymerization reaction at a high temperature of 50-90°C, using tridecane or mesitylene as an organic phase solvent, and post-treating in a sodium hydroxide solution. The reaction time is shortened to 1-15 minutes to form a thin and stable cross-linked quaternary ammonium selective layer.
It significantly improves the water flux, enhances the hydrophilicity of the membrane, enhances its acid resistance in a strong acid environment, achieves membrane stability, solves the stability problem of the polymer membrane existing in the prior art, solves the production efficiency problem existing in the prior art, simplifies production efficiency, greatly improves production efficiency, and solves the problem of long production cycle existing in the prior art.
Smart Images

Figure CN120699303A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer film preparation, and more specifically relates to an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction, and a preparation method and application thereof. Background Art
[0002] Polymer membranes have attracted widespread attention in the separation field due to their simple preparation process, adjustable chemical properties, and ease of scalable application. Polyamide membranes, due to their rigid skeleton structure and adjustable porous structure, are widely used in nanofiltration, ion exchange membranes, fuel cell membranes, and other fields. The commercial polypiperazineamide composite membranes currently in common use are produced by interfacial polymerization of piperazine and trimesoyl chloride on a polysulfone support membrane. Because polypiperazineamide bonds are easily attacked by protons under strongly acidic conditions, resulting in chemical bond breakage, the separation performance of polypiperazineamide membranes decreases sharply, seriously affecting the service life of the membrane and severely hindering the application of membrane technology in separation under acidic conditions.
[0003] To address the acid stability deficiencies of polyamide membranes, researchers have developed solutions such as acid-resistant nanoparticle reinforcement and surface coating. However, due to the chemical nature of polyamide, the separation efficiency of modified membranes will still decline under extremely acidic conditions. In contrast, polyquaternary ammonium salt membranes synthesized through nucleophilic substitution of alkyl halides and tertiary amines, namely the Menshutkin interfacial polymerization reaction, have excellent chemical stability: their cross-linked quaternary ammonium network does not contain easily hydrolyzed amide / ester bonds and can withstand strong acid corrosion. At the same time, the inherent positive charge properties improve the cation retention rate. Pioneering research used pentamethyldiethylenetriamine and 1,3,5-tribromomethylbenzene to polymerize at the alkane-water interface to prepare polyquaternary ammonium salt membranes, but there are still two major bottlenecks: one is the formation of an overly thick selective layer, resulting in low water flux; the other is the slow kinetics of the Menshutkin interfacial polymerization reaction, which requires dozens of hours to form a defect-free network, resulting in extended production cycles and increased costs, seriously restricting the large-scale industrial application of this membrane. Summary of the Invention
[0004] In response to the above defects or improvement needs of the prior art, the present invention provides an acid-resistant polyquaternary ammonium membrane based on Menshutkin interfacial polymerization reaction, and its preparation method and application, thereby solving the technical problems of the prior art in that the polyquaternary ammonium salt membrane has a long production cycle and low water flux due to the slow kinetics of the Menshutkin interfacial polymerization reaction.
[0005] To achieve the above object, according to one aspect of the present invention, a method for preparing an acid-resistant polyquaternary ammonium membrane based on Menschuttekin interfacial polymerization reaction is provided, comprising the following steps:
[0006] (1) dissolving an amine monomer in an aqueous solvent to form an aqueous solution; dissolving a bromomethyl monomer in an organic solvent to form an organic solution;
[0007] (2) soaking the base film in the aqueous solution for a period of time, removing the aqueous solution, and removing the aqueous solution remaining on the surface of the base film;
[0008] (3) coating the organic phase solution on the surface of the base film treated in step (2), and subjecting the base film to an interfacial polymerization reaction at a high temperature of 50 to 90° C. for 1 to 15 minutes to prepare a polyquaternary ammonium film on the base film;
[0009] (4) washing the surface of the polyquaternary ammonium membrane with an organic solvent to remove residual reactants, and then heat-treating it in an oven to obtain the acid-resistant polyquaternary ammonium membrane.
[0010] Preferably, the amine monomer is selected from one or more of N,N,N′,N″,N″-pentamethyldiethylenetriamine, N,N,N′,N′-tetramethylethylenediamine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, 1,4,7,10-tetraazacyclododecane, and piperazine.
[0011] Preferably, the bromomethyl monomer is selected from one or both of 1,3,5-tribromomethylbenzene and 1,2,4,5-tetrabromomethylbenzene.
[0012] Preferably, in the aqueous phase solution, the mass concentration of the amine monomer is 5% to 20%; and in the organic phase solution, the mass concentration of the bromomethyl monomer is 0.05% to 0.2%.
[0013] Preferably, the aqueous phase solvent is deionized water, or a mixed solution of deionized water and other solvents, wherein the other solvents are selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, dimethylacetamide, and N-methylpyrrolidone;
[0014] Preferably, the organic phase solvent is selected from one or more of tridecane and mesitylene.
[0015] Preferably, in step (2), the base film is immersed in the aqueous solution for 5 minutes to 4 hours; in step (4), the heat treatment temperature is 50 to 70° C., and the time is 5 to 10 minutes.
[0016] Preferably, the method further comprises immersing the polyquaternary ammonium membrane treated in step (4) in a sodium hydroxide solution for post-treatment.
[0017] Preferably, the concentration of the sodium hydroxide solution is 0.5 to 2.5 mol / L, and the polyquaternary ammonium membrane is immersed in the sodium hydroxide solution for 3 to 24 hours.
[0018] Preferably, the base membrane is a polysulfone ultrafiltration membrane, a polyethersulfone ultrafiltration membrane, a polyacrylonitrile ultrafiltration membrane, a polyvinylidene fluoride ultrafiltration membrane or a polypropylene (PP) lithium battery separator.
[0019] Preferably, the thickness of the acid-resistant polyquaternary ammonium film is 15-60 nm.
[0020] According to another aspect of the present invention, there is provided an acid-resistant polyquaternary ammonium film produced by the preparation method.
[0021] According to another aspect of the present invention, there is provided an application of the acid-resistant polyquaternary ammonium membrane, which is used as a nanofiltration membrane, anion exchange membrane, or fuel cell membrane.
[0022] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:
[0023] (1) The present invention discloses a method for preparing an acid-resistant polyquaternary ammonium membrane based on the Menschuttekin interfacial polymerization reaction. By limiting the temperature of the interfacial polymerization to a high temperature of 50 to 90°C, the reaction time of the interfacial polymerization is shortened from the traditional tens of hours to 1 to 15 minutes, thereby greatly improving the production efficiency. The shortened reaction time produces a thinner polyquaternary ammonium selective layer, which greatly shortens the transmembrane transmission path of water molecules, thereby further improving the water flux.
[0024] (2) The present invention immerses the polyquaternary ammonium membrane in a sodium hydroxide solution for post-treatment in order to prevent the leakage of bromide ions into the clean water side during the use of the membrane, so that the hydroxide ions in the sodium hydroxide are exchanged with the bromide ions in the synthesized polyquaternary ammonium layer to remove the toxic bromide ions in the polyquaternary ammonium membrane. Sodium hydroxide can accelerate the Br - and OH - exchange, while enhancing the hydrophilicity of the membrane to further increase water flux.
[0025] (3) The organic phase solvent of the present invention is selected from one or more of tridecane and mesitylene. Compared with conventional n-hexane and n-heptane, it has a higher boiling point and is less likely to volatilize during high-temperature reactions. It is more stable. On the one hand, it can avoid the toxicity of volatilization of the organic phase solvent. On the other hand, it can easily produce a stable water-oil interface away from the boiling point. The interfacial polymerization process occurs at the water-oil interface. The stable water-oil interface can avoid the formation of a thicker film or local defects in the film.
[0026] (4) The acid-resistant polyquaternary ammonium membrane prepared by the Menschutkin interfacial polymerization reaction of the present invention has a cross-linked quaternary ammonium network and does not contain easily hydrolyzed amide bonds. The polyquaternary ammonium membrane has an extremely strong positive charge. The positive charge provided by the strong electrolyte quaternary ammonium is more stable to pH changes than the weak electrolyte primary amine, tertiary amine, etc., and can maintain long-term stability in a strong acid environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a preparation flow chart of the present invention.
[0028] Figure 2 It is a Fourier attenuated total reflection infrared spectrum of the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization reaction described in the present invention, wherein M0 is a polysulfone ultrafiltration base membrane, and M1-M3 correspond to the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization reaction prepared in Examples 1-3 respectively.
[0029] Figure 3 These are scanning electron microscope surface images, atomic force microscope scanning images, and scanning electron microscope cross-sectional images of the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization reaction described in the present invention. M1-M3 correspond to the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization reaction prepared in Examples 1-3, respectively.
[0030] Figure 4 The salt retention rate (%) and water flux (L m) of the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization prepared in Example 1 for four salt solutions (concentration 2g / L) of MgCl2, MgSO4, Na2SO4, and NaCl -2 h -1 bar -1 ).
[0031] Figure 5 The figure shows the change in the MgCl2 solution rejection rate of the acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction prepared in Example 1 during immersion in a 1.5 mol / L sulfuric acid solution for 40 days. DETAILED DESCRIPTION
[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely for the purpose of explaining the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.
[0033] The following are the corresponding performance testing methods in the test data of each embodiment and comparative example.
[0034] (1) Nanofiltration performance of aqueous solution
[0035] The nanofiltration performance of aqueous solutions of acid-resistant polyquaternary ammonium membranes based on menshutkin interfacial polymerization was tested on a cross-flow filtration device. Before the flux test, each new membrane was stabilized with pure water at a pressure of 5 bar for 30 minutes. Subsequently, the test pressure was 5 bar and the test temperature was 25±0.5℃ at a cross-flow rate of 45 L h-1. w ,L m -2h -1 bar -1 ) is calculated according to the following formula:
[0036]
[0037] Where V is the volume of permeate (L), A is the effective area of the test membrane (m 2 ), Δt is the time taken to collect the required volume of permeate (h), and ΔP is the transmembrane pressure (bar).
[0038] The calculation formula of salt retention rate (R, %) is as follows:
[0039]
[0040] Where c p and c f are the salt concentrations in the permeate and feed solutions, respectively. The feed solution is 2 g L -1 of magnesium chloride solution.
[0041] (2) Nanofiltration performance resistant to organic solvents
[0042] The organic solvent resistance nanofiltration performance of acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization was tested on a dead-end filtration device. Before the flux test, each new membrane was stabilized with pure water at 5 bar pressure for 30 minutes. The test pressure was 5 bar and the test temperature was 25±0.5℃. o ,L m -2 h -1 bar -1 ) is calculated according to the following formula:
[0043]
[0044] Where V is the volume of permeate (L), A is the effective area of the test membrane (m 2 ), Δt is the time taken to collect the required volume of permeate (h), and ΔP is the transmembrane pressure (bar).
[0045] The calculation formula of salt retention rate (R, %) is as follows:
[0046]
[0047] Where c p and c f are the dye concentrations in the permeate and feed solutions, respectively. The feed solution is 20 μmol L -1 Congo red / methanol solution.
[0048] (3) Anion exchange membrane performance
[0049] The ion exchange capacity of the acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction was determined by titration. The membrane sample (0.5 g) was soaked in hydrochloric acid (0.1 mol / L) at 25°C for 24 hours and manually titrated with sodium hydroxide (0.1 mol / L) solution until the solution pH was neutralized (pH = 7.0). The ion exchange capacity of the membrane (IEC, mmol g -1 ) is calculated by the following formula:
[0050]
[0051] Where C HCl and C NaOH are the concentrations of hydrochloric acid and sodium hydroxide, V HCl and V NaOH are the volumes of hydrochloric acid and sodium hydroxide respectively.
[0052] The present invention uses the AC impedance method to test the ionic resistance of the acid-resistant polyquaternary ammonium membrane based on the Menshutkin interfacial polymerization reaction. The measurement frequency range is 100 MHz to 1 MHz. The measured resistance curve is fitted and the ionic conductivity (σ) is calculated by the following formula:
[0053]
[0054] Where d is the distance between the electrodes, R is the resistance of the membrane, and S is the cross-sectional area of the membrane.
[0055] Example 1
[0056] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction, the preparation flow chart is as follows Figure 1 As shown, the following steps are included:
[0057] (1) Weigh 1 g of N,N,N′,N″,N″-pentamethyldiethylenetriamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0058] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0059] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction; the polyquaternary ammonium salt selective layer has a thickness of 30 nm;
[0060] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0061] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0062] Example 2
[0063] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0064] (1) Weigh 1 g of N,N,N',N'-tetramethylethylenediamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0065] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0066] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction; the polyquaternary ammonium salt selective layer has a thickness of 48 nm;
[0067] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0068] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0069] Example 3
[0070] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0071] (1) Weigh 1 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0072] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0073] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction; the polyquaternary ammonium salt selective layer has a thickness of 28 nm;
[0074] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0075] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0076] Example 4
[0077] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0078] (1) Weigh 2 g of 1,4,7,10-tetraazacyclododecane and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of mesitylene to form an organic phase solution;
[0079] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0080] (3) immersing the treated base film in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction;
[0081] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0082] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0083] Example 5
[0084] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0085] (1) Weigh 0.5 g of piperazine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.19 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0086] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0087] (3) immersing the treated base film in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction;
[0088] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0089] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0090] Example 6
[0091] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0092] (1) Weigh 1 g of N,N,N′,N″,N″-pentamethyldiethylenetriamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,2,4,5-tetrabromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0093] (2) immersing the PP lithium battery separator in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0094] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction; the polyquaternary ammonium salt selective layer has a thickness of 60 nm;
[0095] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0096] (5) The membrane obtained in step (3) was immersed in a 0.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0097] Example 7
[0098] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0099] (1) Weigh 1 g of piperazine and dissolve it in 10 mL of a water / dimethyl sulfoxide mixture (water:dimethyl sulfoxide = 4:6) to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0100] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0101] (3) immersing the treated base film in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction;
[0102] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0103] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0104] Example 8
[0105] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0106] (1) Weigh 1 g of N,N,N′,N″,N″-pentamethyldiethylenetriamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of mesitylene to form an organic phase solution;
[0107] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0108] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction; the polyquaternary ammonium salt selective layer has a thickness of 30 nm;
[0109] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residues on the surface, and then heat-treated in an oven at 70° C. for 10 minutes;
[0110] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 3 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0111] Example 9
[0112] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0113] (1) Weigh 1 g of N,N,N′,N″,N″-pentamethyldiethylenetriamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0114] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0115] (3) immersing the treated base film in the organic phase solution obtained in step (1) and reacting at 50° C. for 15 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction;
[0116] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0117] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0118] Example 10
[0119] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0120] (1) Weigh 1 g of N,N,N′,N″,N″-pentamethyldiethylenetriamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0121] (2) immersing the polysulfone ultrafiltration base membrane in the aqueous solution obtained in step (1) for 5 minutes, removing the solution and removing the residual liquid on the surface with an air knife;
[0122] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at 90° C. for 1 minute to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction; the polyquaternary ammonium salt selective layer has a thickness of 15 nm;
[0123] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0124] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0125] Example 11
[0126] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0127] (1) Weigh 2 g of N,N,N′,N″,N″-pentamethyldiethylenetriamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0128] (2) immersing the polysulfone ultrafiltration membrane in the aqueous solution obtained in step (1) for 4 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0129] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at 70° C. for 2 minutes to form a cross-linked polyquaternary ammonium salt selective layer through a menshutkin interfacial polymerization reaction; the polyquaternary ammonium salt selective layer has a thickness of 30 nm;
[0130] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residues on the surface, and then heat-treated in an oven at 70° C. for 10 minutes;
[0131] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0132] Comparative Example 1
[0133] A method for preparing an acid-resistant polyquaternary ammonium film based on menshutkin interfacial polymerization reaction comprises the following steps:
[0134] (1) Weigh 1 g of N,N,N′,N″,N″-pentamethyldiethylenetriamine and dissolve it in 10 mL of deionized water to form an aqueous phase solution; weigh 0.75 g of 1,3,5-tribromomethylbenzene and dissolve it in 50 mL of tridecane to form an organic phase solution;
[0135] (2) immersing the PP lithium battery separator in the aqueous solution obtained in step (1) for 2 hours, removing the solution and removing the residual liquid on the surface with an air knife;
[0136] (3) immersing the treated basement membrane in the organic phase solution obtained in step (1) and reacting at room temperature for 24 hours to form a cross-linked polyquaternary ammonium salt selective layer through menshutkin interfacial polymerization reaction; the thickness of the polyquaternary ammonium salt selective layer is 346 nm;
[0137] (4) The membrane obtained in step (3) was rinsed with tridecane to remove the unreacted residue on the surface, and then heat-treated in an oven at 70° C. for 5 minutes;
[0138] (5) The membrane obtained in step (3) was immersed in a 2.5 mol / L sodium hydroxide solution and post-treated for 24 hours to finally obtain an acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction.
[0139] The aqueous solution nanofiltration performance of the acid-resistant polyquaternary ammonium membranes based on the Menshutkin interfacial polymerization reaction prepared in Examples 1-11 and Comparative Example 1 is listed in Table 1. While significantly shortening the membrane preparation time, the present invention significantly improved the water flux of all examples compared to the comparative example, and most examples had a retention rate ≥95% (only two examples were slightly lower), demonstrating superior overall performance.
[0140] Table 1
[0141]
[0142]
[0143] The aqueous solution nanofiltration performance of the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization prepared in Example 1 and Comparative Example 1 is listed in Table 2. The methanol flux of Example 1 is 158% higher than that of Comparative Example 1, and the Congo red rejection rate is higher than that of the Comparative Example, indicating a significant improvement in performance.
[0144] Table 2
[0145]
[0146] The performance of the acid-resistant polyquaternary ammonium membrane based on the menshutkin interfacial polymerization reaction prepared in Example 1 and Comparative Example 1 as anion exchange membrane is listed in Table 3. It can be seen from the data in Table 3 that the present invention shortens the reaction time while having no significant effect on the ion exchange capacity and ion conductivity of the composite membrane, and even improves them to a certain extent.
[0147] Table 3
[0148]
[0149] Figure 2 This is the Fourier attenuated total reflection infrared spectrum of the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization reaction described in the present invention, wherein M0 is a polysulfone ultrafiltration base membrane, and M1-M3 correspond to the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization reaction prepared in Examples 1-3 respectively. The Fourier attenuated total reflection infrared spectrum shows that at 1670 cm -1 and 1386cm -1 The presence of characteristic peaks at 370 nm and 370 nm corresponds to the cross-linked quaternary ammonium and unreacted tertiary amine, respectively. These peaks were not observed in the PSF support, indicating the successful formation of the polyquaternium selective layer.
[0150] Figure 3 The following are scanning electron microscope (SEM) surface images, atomic force microscope (AFM) scanning images, and SEM cross-sectional images of the acid-resistant polyquaternary ammonium membranes based on the Menshutkin interfacial polymerization reaction described herein. M1-M3 correspond to the acid-resistant polyquaternary ammonium membranes based on the Menshutkin interfacial polymerization reaction prepared in Examples 1-3, respectively. The SEM surface images show that the surfaces of all membranes are continuous and defect-free, while the AFM scanning images confirm nanoscale smoothness (Ra values below 7 nanometers). The SEM cross-sectional images clearly demonstrate the layered structure between the selective layer and the base membrane.
[0151] Figure 4 The salt retention rate (%) and water flux (L m) of the acid-resistant polyquaternary ammonium membrane based on menshutkin interfacial polymerization prepared in Example 1 for four salt solutions (concentration 2g / L) of MgCl2, MgSO4, Na2SO4, and NaCl -2 h -1 bar -1 The retention rates were as follows: MgCl2 (97.17%) > NaCl (82.67%) > MgSO4 (41.78%) > Na2SO4 (33.33%). The large number of quaternary ammonium groups within the membrane imparts a positive charge to the membrane surface over a wide pH range. The membrane repeles divalent cations and attracts divalent anions through electrostatic interactions.
[0152] Figure 5The following table shows the change in MgCl₂ solution rejection of the acid-resistant polyquaternary ammonium membrane based on the Menshutkin interfacial polymerization reaction prepared in Example 1 during immersion in a 1.5 mol / L sulfuric acid solution for 40 days. The MgCl₂ retention of the polyquaternary ammonium membrane remained above 95% after immersion in the 1.5 mol / L sulfuric acid solution for 40 days.
[0153] It will be easily understood by those skilled in the art that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction, characterized in that: The following steps are involved: (1) dissolving an amine monomer in an aqueous solvent to form an aqueous solution; dissolving the bromomethyl monomer in an organic phase solvent to form an organic phase solution; (2) soaking the basement membrane in the aqueous solution, and removing the aqueous solution remaining on the surface of the basement membrane after taking it out; (3) coating the organic phase solution on the surface of the base film treated in step (2), and subjecting the base film to an interfacial polymerization reaction at a high temperature of 50 to 90° C. for 1 to 15 minutes to prepare a polyquaternary ammonium film on the base film; (4) washing the surface of the polyquaternary ammonium membrane with an organic solvent to remove residual reactants, and then performing heat treatment to obtain the acid-resistant polyquaternary ammonium membrane.
2. The method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction according to claim 1, characterized in that: The amine monomer is selected from one or more of N,N,N′,N″,N″-pentamethyldiethylenetriamine, N,N,N′,N′-tetramethylethylenediamine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, 1,4,7,10-tetraazacyclododecane, and piperazine.
3. The method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction according to claim 1, characterized in that: The bromomethyl monomer is selected from one or two of 1,3,5-tribromomethylbenzene and 1,2,4,5-tetrabromomethylbenzene.
4. The method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction according to claim 1, characterized in that: In the aqueous phase solution, the mass concentration of the amine monomer is 5% to 20%; in the organic phase solution, the mass concentration of the bromomethyl monomer is 0.05% to 0.2%.
5. The method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction according to claim 1, characterized in that: The aqueous phase solvent is deionized water, or a mixed solution of deionized water and other solvents, wherein the other solvents are selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; The organic phase solvent is selected from one or more of tridecane and mesitylene.
6. The method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction according to claim 1, characterized in that: In step (2), the base film is immersed in the aqueous solution for 5 minutes to 4 hours; in step (4), the heat treatment temperature is 50 to 70° C. and the time is 5 to 10 minutes.
7. The method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction according to claim 1, characterized in that: After step (4), the method further includes immersing the polyquaternary ammonium membrane in a sodium hydroxide solution for post-treatment.
8. The method for preparing an acid-resistant polyquaternary ammonium film based on Menschuttekin interfacial polymerization reaction according to claim 7, characterized in that: The concentration of the sodium hydroxide solution is 0.5 to 2.5 mol / L, and the polyquaternary ammonium membrane is immersed in the sodium hydroxide solution for 3 to 24 hours.
9. The acid-resistant polyquaternary ammonium film prepared according to the preparation method according to any one of claims 1 to 8.
10. The use of the acid-resistant polyquaternary ammonium membrane according to claim 9, characterized in that: It is used as nanofiltration membrane, anion exchange membrane, and fuel cell membrane.
Citation Information
Cited By
Method for preparing polyquaternary ammonium nanofiltration membrane based on Portland reaction interfacial polymerization and application of polyquaternary ammonium nanofiltration membrane
CN120079267A
Method for preparing polyquaternary ammonium nanofiltration membrane based on door shut gold reaction interface polymerization and application
CN120079267B
Monovalent selective cation exchange membrane with acid stability and method of making same
CN122682436A